2010
DOI: 10.1007/s00381-010-1181-3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric high-flow, cervical spinal, macro-arteriovenous fistula, treated with the endovascular cotton candy glue injection technique

Abstract: A 3-year-old boy presented to our hospital with progressive neurological deficits. Spinal magnetic resonance imaging (MRI) revealed a perimedullary macro-arteriovenous fistula (PMAVF) resulting in a large venous pouch within the parenchyma of the lower cervical spinal cord. Transarterial varix embolization of the fistula from the venous side was performed using N-butyl cyanoacrylate with tantalum powder. Postembolization angiography confirmed obliteration of the fistula, and MRI revealed thrombosis and reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…There are various classifications of spinal vascular malformations. The most common classification by Rosenblum divides spinal vascular malformations into four categories, which are type I (Dural arteriovenous fistula (AVF), type II (Glomus arteriovenous malformation (AVM)), type III (Juvenile AVM), and type IV (Peri-medullary AVF) [4] , [5] , [6] ]. Type I is the most common, accounting for 80%-85% of all spinal vascular malformations, while type IV is rare [4] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are various classifications of spinal vascular malformations. The most common classification by Rosenblum divides spinal vascular malformations into four categories, which are type I (Dural arteriovenous fistula (AVF), type II (Glomus arteriovenous malformation (AVM)), type III (Juvenile AVM), and type IV (Peri-medullary AVF) [4] , [5] , [6] ]. Type I is the most common, accounting for 80%-85% of all spinal vascular malformations, while type IV is rare [4] .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, because of the high flow of fistula, the transition was marked by the formation of a large venous pouch. PMAVF in the ventral area of the spinal cord is generally subpial and is supplied by the anterior spinal artery, whereas if it is subarachnoid, it is generally supplied by the posterolateral spinal artery [5] . This case was unique, because the large fistula was supplied by only 1 feeder artery, which was anterior radiculomedullary artery, and drain into a large venous pouch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous clinical evidence has indicated that lesion size and blood flow may be related to the spectrum of pathophysiological mechanisms of PMAVFs (eg, venous congestion, bleeding or spinal cord compression), which can result in diverse clinical characteristics 2 3 6. Additionally, when developing treatment strategies for specific PMAVF patients, these parameters are also important considerations 4–8. Therefore, the optimal classification of PMAVFs should take the lesion size and blood flow into account 9–11.…”
Section: Introductionmentioning
confidence: 99%